Can Changes in Financial Performance Be Used in the Diagnosis of Neurocognitive Disorders? A Systematic Review of Findings from Greece - Vaitsa Giannouli (Brain Sciences)
Background/Objectives: Elder abuse, and more specifically financial exploitation, is expected to be a major problem in modern societies as the worldwide population is getting older. Neuropsychological protocols regarding financial capacity assessment are the only available window allowing us to view the cognitive–emotional–behavioral strengths/deficits and vulnerabilities of individuals. Given the paucity of relevant research in Greece in the most vulnerable individuals such as older adults suffering from neurocognitive disorders (NCDs), this systematic review attempts to investigate whether NCDs impair financial capacity and to highlight the most important factors that can predict financial incapacity in Greek older patients and the likelihood of financial abuse. Methods: A systematic search was conducted in Embase, PsycINFO, and PubMed. Results: The search identified n = 21 relevant research articles. The synthesis of available evidence supports that financial incapacity is clearly demonstrated in the group of Greek older adults suffering from NCDs of different severity and etiology; thus, such changes can assist diagnosis, treatment, and care of these individuals, but the implications for elder abuse in the Greek cultural context have not been examined in detail so far. Conclusions: Given the unique source of information that neuropsychological assessments represent by revealing the importance of factors such as arithmetic cognition and relevant brain volume changes in the left angular gyrus, depressive mood, apathy, frailty, vascular risk factors, and financial illiteracy, forensic neuropsychology can play a vital role in protecting older individuals from financial abuse.